2019
DOI: 10.1039/c9ce00495e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanocrystalline strontium titanate by a sol–gel assisted solid phase method and its formation mechanism and photocatalytic activity

Abstract: Strontium titanate (SrTiO3) with a perovskite structure is widely applied to hydrogen production by photolysis water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…The reason for SrCO 3 phase depletion with increasing temperature is still unclear. We believe that the SrCO 3 reacts directly with the titanium species to yield the SrTiO 3 phase, as observed before . The intensity ratios of the (110) characteristic peak to the (100) peak, i.e., I (110) / I (100) , presented an exceptional temperature dependency, as indicated in Figure d.…”
Section: Results and Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The reason for SrCO 3 phase depletion with increasing temperature is still unclear. We believe that the SrCO 3 reacts directly with the titanium species to yield the SrTiO 3 phase, as observed before . The intensity ratios of the (110) characteristic peak to the (100) peak, i.e., I (110) / I (100) , presented an exceptional temperature dependency, as indicated in Figure d.…”
Section: Results and Discussionsupporting
confidence: 65%
“…We believe that the SrCO 3 reacts directly with the titanium species to yield the SrTiO 3 phase, as observed before. 46 The intensity ratios of the (110) characteristic peak to the (100) peak, i.e., I (110) / I (100) , presented an exceptional temperature dependency, as indicated in Figure 4 d. This ratio increases up to 750 °C and becomes nearly invariant for higher temperatures, strongly suggesting a favored growth of the {110} facets ( Figure 4 d). The lattice parameter ( a 0 ) and the crystallite size ( D hkl ) were calculated using Bragg’s law and the Scherrer equation (see the Supplementary Information ) from the highest intensity peak, i.e., (110) direction and are also displayed in Figure 4 d. The lattice parameter a 0 decreased up to 750 °C, resulting in the unit cell volume contraction; hence, a crystal structure with shorter bond lengths is formed.…”
Section: Results and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Important research endeavors have recently been devoted to the preparation of materials by using various chemical approaches. [11][12][13] Vijatovic et al [14] reported that the synthesis process has a significant influence on the major properties of the ceramics. Indeed, the morphology of powders consists of particles and their shape and size, the dimensions are related to the synthesis method.…”
Section: Introductionmentioning
confidence: 99%
“…Photolysis of water for hydrogen production and photocatalytic degradation of organic pollutants by sunlight have positive effects on energy and environmental problems. [1] At present, the common semiconductor photocatalysts, such as TiO 2 , SrTiO 3 [2] and BaTiO 3 [3] , has the advantages of nontoxic, good stability, high photocatalytic activity. However, with a band gap as high as 3.1-3.3 eV, they can only absorb ultraviolet light.…”
Section: Introductionmentioning
confidence: 99%